Conservative Management of Liver Perforation During Percutaneous Nephrolithotomy: Case Couplet Presentation - Rai, Arun (J Endourol Case Rep, 2020)
Percutaneous nephrolithotomy (PCNL) remains the recommended intervention for large kidney stones, major complications, although rare, are between 1% and 7%. Literature regarding liver injury during PCNL is sparse, and many incidences occur unnoticed. In general, most liver injuries can be treated conservatively when compared with other organ injury sustained during PCNL. Despite this, there is still significant potential for intraperitoneal bleeding as well as possible hemodynamic instability that may result secondary to the inadvertent access. Our team describes two cases of liver injury during PCNL with focus on presentation and injury management. Both cases were treated conservatively through close clinical monitoring and delayed removal of nephrostomy tube. Both liver injuries were diagnosed primarily through postprocedure axial CT imaging. In general, risk factors include supracostal access, particularly at or above the 11th rib, as well as hepatomegaly. Despite that liver injury is a rare complication of right-sided PCNL, outcomes can result in significant blood loss not diagnosed. We present in this study two instances of effective conservative management of liver injury after PCNL.